Hyperinflation of bronchi in vitro impairs bronchodilation to simulated breathing and increases sensitivity to contractile activation. Issue 8 (20th February 2018) - Cairncross, Alvenia; Noble, Peter B.; McFawn, Peter K.
ABSTRACT: Background and objective: Lung hyperinflation and reduced bronchodilation to deep inspiration (DI) are features of chronic obstructive pulmonary disease (COPD). Hyperinflation might impair the ability of a DI to stretch airway smooth muscle (ASM), as the bronchi operate at a stiff region of the pressure–volume curve. Methods: Bronchial segments from pig lungs were mounted in an organ bath and equilibrated at either 5 cm H2 O (control) or 20 cm H2 O (hyperinflated) transmural pressure (Ptm ). Cumulative dose–response curves to acetylcholine (ACh) were performed to determine maximal response (Emax ) and sensitivity under static conditions (fixed Ptm ) or during simulated breathing (Δ10 cm H2 O Ptm at 0.25 Hz). The effect of hyperinflation on ASM contraction was further examined in bronchial rings contracted at a short ASM length (reference length, Lref ) or stretched by an additional 30% (length 1.3 times the Lref, 1.3Lref ). Results: Oscillatory loads halved Emax from 61.0 ± 3.8 to 29.7 ± 4.4 cm H2 O ( P < 0.0001) in control bronchial segments, but only from 40.0 ± 2.5 to 31.2 ± 2.4 cm H2 O ( P < 0.05) in hyperinflated segments. The percentage reduction in active pressure with oscillation was less in hyperinflated compared with control segments ( P < 0.01). Sensitivity was not altered by oscillation in either hyperinflated or control segments; however, hyperinflated segments were more sensitive ( P < 0.05). The effect of inflation on sensitivity was confirmed using bronchial rings where stretched rings were more sensitive than unstretched rings ( P < 0.01). Conclusion: Hyperinflated bronchi exhibit reduced bronchodilation to breathing and increased sensitivity to bronchoconstrictor stimuli. Findings suggest that hyperinflation may directly alter airway function by reducing the protective effects of DI and initiating contraction at low doses of contractile stimuli. Abstract : We investigated the effect of lung hyperinflation on mechanical properties of airways isolated from pig lungs. Findings suggest that hyperinflation impairs the bronchodilatory capacity of breathing and increases the sensitivity of the airway smooth muscle to contractile mediators, both of which may contribute to airflow limitation in obstructive disease. See related Editorial